ANALISA KETERSEDIAAN DATA SDGs DI KABUPATEN INDRAGIRI HULU - Gerhana Adjie , Roberta Zulfhi Surya (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Presidential Decree No. 59 Year 2017 on the implementation of the SDGs in Indonesia is mandatory and request the stakeholder’s commitment. Integrating SDGs into development planing requires reliable data and statistical. This researsch aims to determine the avaibility of data that in line with SDGs. Base on this research obtained information that available 65 data in line with SDGs Indicator, consists of 60 data items TIER I and 5 data items will be Developed indicator cause out of the district autority.